Penyelesaian Peselisihan Perjanjian Kerja Sama antara Asosiasi Bongkar Muat dengan Koperasi Tenaga Bongkar Muat Upaya Karya - Gomgom Siregar (Mahesa Research Center, 2019)
The purpose of this paper is to describe the factors causing disputes in a collaboration, procedures for the resolution of cooperation disputes and settlement through non-litigation procedures. This type of research used in this research is normative legal research with the focus of problems related to how the dispute resolution of cooperation between loading and unloading associations with the labor force loading and unloading effort cooperatives. Based on the results of the study, it is known that the settlement of cooperation disputes between the stevedoring association with the stevedoring labor cooperative can be carried out through litigation and non-litigation procedures.